Analysis of Answer Processes Based on Mathematical Creative Thinking Abilities in Contextual Teaching and Learning - Lois Oinike Tambunan; Sahat Saragih; Elvis Napitupulu (Cita konsultindo, 2025)
This study aims to analyze and determine: (1) the level of students' mathematical creative thinking ability when taught using the Contextual Teaching and Learning (CTL) model; (2) a description of the students' creative thinking process in mathematics during the learning process using the Contextual Teaching and Learning (CTL) model. This research is a descriptive qualitative study. The subjects of this research were 30 students of class VIII-2 from SMP Negeri 1 Pematangsiantar. The research findings are as follows: (1) 18 students in the high-ability category were classified as highly creative, fulfilling 3 indicators of creative thinking: fluency, flexibility, and novelty; 9 students in the moderate-ability category were classified as creative, fulfilling 2 indicators of creative thinking: fluency and flexibility; and 3 students in the low-ability category were classified as less creative, fulfilling only 1 indicator of creative thinking: fluency. These results indicate that students demonstrated an improvement in creative thinking abilities after being taught using the Contextual Teaching and Learning (CTL) model. It is also hoped that the Contextual Teaching and Learning model can be applied in the learning process to enhance students' mathematical creative thinking abilities.: Answering Process; Contextual Teaching and Learning; Creative Thinking.